2013
DOI: 10.3171/2013.8.spine12804
|View full text |Cite
|
Sign up to set email alerts
|

Clinically important deterioration in patients undergoing lumbar spine surgery: a choice of evaluation methods using the Oswestry Disability Index, 36-Item Short Form Health Survey, and pain scales

Abstract: Object Health-related quality of life (HRQOL) measures have become the mainstay for outcome appraisal in spine surgery. Clinically meaningful interpretation of HRQOL improvement has centered on the minimum clinically important difference (MCID). The purpose of this study was to calculate clinically important deterioration (CIDET) thresholds and determine a CIDET value for each HRQOL measure for patients undergoing lumbar fusion. Methods Seven hundred twenty-two patients (248 males, 127 smokers, mean age 60.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…For instance, severely disabled patients will require disproportionally greater improvements than the less disabled, not to consider the surgery as failed. This is in accordance with findings of other studies and illustrates the importance of taking into account the baseline score while interpreting PROM change scores, regardless of using absolute or percentage change scores [18,41]. Consequently, one should adjust for the baseline score when using such outcome criteria in clinical trials and risk factor analyses.…”
Section: Methodological Challengessupporting
confidence: 89%
See 1 more Smart Citation
“…For instance, severely disabled patients will require disproportionally greater improvements than the less disabled, not to consider the surgery as failed. This is in accordance with findings of other studies and illustrates the importance of taking into account the baseline score while interpreting PROM change scores, regardless of using absolute or percentage change scores [18,41]. Consequently, one should adjust for the baseline score when using such outcome criteria in clinical trials and risk factor analyses.…”
Section: Methodological Challengessupporting
confidence: 89%
“…In a smaller single-center study from 2013, Gum et al tried to define clinically important deterioration among patients operated with lumbar fusion for various diagnoses, but found it difficult to define cutoffs. They concluded that a larger patient population was needed to identify accurate cutoffs, since worsening is a relatively rare event [41]. We have used a much larger and more condition-specific cohort.…”
Section: Limitations and Strengths Of This Studymentioning
confidence: 99%
“…Variations in scores using different methodologies (i.e. anchor based vs distributional) have previously been highlighted in the orthopaedic spinal literature [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the minimum clinically important difference (MICD) for the ODI in lumbar spine surgery patients (10,16,(28)(29)(30). The cut-off value often is interpreted as a significant change for both clinically improvement and deterioration.…”
Section: Original Articlementioning
confidence: 99%